2021
DOI: 10.1186/s40478-021-01302-7
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 associates with increased risk of severe COVID-19, cerebral microhaemorrhages and post-COVID mental fatigue: a Finnish biobank, autopsy and clinical study

Abstract: Apolipoprotein E ε4 allele (APOE4) has been shown to associate with increased susceptibility to SARS-CoV-2 infection and COVID-19 mortality in some previous genetic studies, but information on the role of APOE4 on the underlying pathology and parallel clinical manifestations is scarce. Here we studied the genetic association between APOE and COVID-19 in Finnish biobank, autopsy and prospective clinical cohort datasets. In line with previous work, our data on 2611 cases showed that APOE4 carriership associates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 46 publications
(42 reference statements)
2
62
0
4
Order By: Relevance
“…Imaging in these patients was unremarkable, but this phenotype warrants further investigation, including serological and CSF characterization and advanced imaging modalities, especially given recent findings on the association of certain alleles (APOE4) and presenting with severe COVID-19 or post-COVID fatigue. 23 In our study, most patients reported mild or moderate COVID-19 infection, with only 8.9% requiring hospitalization. This is consistent with previous data showing that nonhospitalized patients, many with a mild infection, still experience long-haul neuro-PASC symptoms months after infection.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Imaging in these patients was unremarkable, but this phenotype warrants further investigation, including serological and CSF characterization and advanced imaging modalities, especially given recent findings on the association of certain alleles (APOE4) and presenting with severe COVID-19 or post-COVID fatigue. 23 In our study, most patients reported mild or moderate COVID-19 infection, with only 8.9% requiring hospitalization. This is consistent with previous data showing that nonhospitalized patients, many with a mild infection, still experience long-haul neuro-PASC symptoms months after infection.…”
Section: Discussionmentioning
confidence: 47%
“…We observed a rare but concerning phenotype of tremor, ataxia, and cognitive dysfunction in a subset of patients without any known prior neurologic disease. Imaging in these patients was unremarkable, but this phenotype warrants further investigation, including serological and CSF characterization and advanced imaging modalities, especially given recent findings on the association of certain alleles (APOE4) and presenting with severe COVID‐19 or post‐COVID fatigue 23 …”
Section: Discussionmentioning
confidence: 91%
“…Recent studies in mice found that ApoE in brain pericytes regulate endothelial function by modulating basement membrane components ( Yamazaki et al, 2020 ). APOE ε 4 increases the severity of infections such as herpes simplex virus type 1 (HSV-1) ( Linard et al, 2020 ; Zhao et al, 2020 ), HIV-1 ( Corder et al, 1998 ), and SARS-CoV-2 ( Kurki et al, 2021 ) and worsens cognitive impairment.…”
Section: The Human Element Of Alzheimer’s Diseasementioning
confidence: 99%
“…This is demonstrated by the evidence of vascular and aberrant immune reaction-related factors [35]. Furthermore, after contracting COVID-19, the risk of being hospitalized is doubled in patients homozygous for APOEε4, a known risk factor for AD [36], that results in a predictor of doubled risk of severe infection and of quadruple risk of mortality [37][38][39]. The so-called, COVID-19-induced "brain fog" can be long-lasting, accelerating cognitive decline in AD patients, and this may be supported by the western blotting evidence of increased levels of ACE-2 in AD patients' hippocampal tissue [40].…”
Section: Neurobiological Common Ground Of Covid-19 and Dementiamentioning
confidence: 99%